Genetic Diversity and Natural Selection of Plasmodium vivax Duffy Binding Protein-II From China-Myanmar Border of Yunnan Province, China - Shi, Tian-Qi; Shen, Hai-Mo; Chen, Shen-Bo; Kassegne, Kokouvi; Cui, Yan-Bing; Xu, Bin; Chen, Jun-Hu; Zheng, Bin; Wang, Yue (Frontiers in Microbiology, 2021)
Malaria incidence have declined dramatically over the past decade and, China had been certified malaria-free for indigenous cases within its borders in 2021. However, the presence of malaria in border areas and the importation of cases of malaria parasites are major challenges for the consolidation of the achievements made by China. Plasmodium vivax Duffy binding protein (PvDBP) plays an essential role in erythrocyte invasion by malaria merozoites. PvDBP is a prime blood-stage vaccine candidate antigen against P. vivax, but its polymorphic nature represents a major obstacle to successfully design an protective vaccine against vivax malaria. In this study, we investigated the genetic polymorphism and natural selection of the N-terminal cysteine-rich region of PvDBP (PvDBP-II) among 124 P. vivax isolates collected from China-Myanmar border (CMB) in Yunnan Province, China, during 2009-2011. In addition, 85 pvdbp-II sequences from P. vivax population of eastern Myanmar were retrieved from GenBank and were used for comparative analysis of genetic diversity, and recombination and population structure. Totally, 22 single nucleotide polymorphisms reflected in 20 non-synonymous and two synonymous were identified. The overall nucleotide diversity of PvDBP-II from the 124 CMB isolates was 0.0059 with 21 haplotypes identified (Hd=0.91). The differences between the rates of non-synonymous and synonymous mutations suggested that PvDBP-II had evolved under positive natural selection. Population structure analysis of the CMB and eastern Myanmar isolates optimally grouped into five sub-populations (K=5). Our results confirm that PvDBP-II of CMB isolates displayed polymorphisms caused by mutation, recombination, and positive selection. Along with the more effective malaria control measures, the population structure in different areas where malaria is endemic had changed. In conclusion, findings from this study advance knowledge of the understanding of the dynamic of P. vivax population, which will contribute to guide the rational design of PvDBP-II based vaccine.ne.